Tumor-Associated Macrophages: New Horizons for Pituitary Adenoma Researches - Han, Changxi; Lin, Shaojian; Lu, Xingyu; Xue, Li; Wu, Zhe Bao (Frontiers in Endocrinology, 2021)
Macrophages are one of the most common infiltrating immune cells and an essential component of tumor microenvironment. Macrophages and the soluble cytokines and chemokines produced play an important role in tumorigenesis, progression, invasion and metastasis in solid tumors. Despite the multiple studies in other solid tumors, there is little known about macrophages in pituitary adenomas. Recently, studies about pituitary adenoma-infiltrated macrophages have been emerging, including the immunohistochemical and immunophenotypic analysis of the pituitary adenomas and further studies into the mechanism of the crosstalk between macrophages and tumor cells in vivo and in vitro. These studies have offered us new insights into the polarization of macrophages and its role in tumorigenesis, progression and invasion of pituitary adenomas. This review describes the advances in the field of pituitary adenoma-infiltrated macrophages and the prospect of targeting macrophages as cancer therapy in pituitary adenoma.